Real-World Data of Triplet Combination of Trastuzumab, Lapatinib, and Chemotherapy in HER2-Positive Metastatic Breast Cancer: A Multicenter Retrospective Study - Li, Yi; Gong, Chengcheng; Lu, Qianyi; Zhou, Zhaochun; Luo, Ting; Li, Wei; Li, Gang; Ge, Rui; Xu, Fei; Wang, Biyun (Frontiers in Oncology, 2020)
Introduction: Combination of trastuzumab(T) and lapatinib(L) has been showed to significantly improve the prognosis of HER2+ heavily pretreated metastatic breast cancer (MBC). Whether TL combined chemotherapy (TLC) can further improve the efficacy in HER2+ MBC remains to be further studied. The aim of the study was to report the first real-world data of TLC in HER2+ MBC, including the efficacy, safety and treatment patterns. Methods: Patients with HER2+ MBC treated with TLC in 5 institutions of China from September 2013 to July 2019 were included. Progression free survival (PFS), objective response rate (ORR), overall survival (OS), toxicity profile and treatment pattern were reported. Results: A total of 285 patients were included. 88.8% were exposed to trastuzumab and 49.2% received 2 or more lines of systematic therapy before TLC previously. The most common chemotherapy regimens combined with TL were capecitabine (40.7%) and vinorelbine (21.4%) and almost 1/3 received maintenance treatment after TLC. Median PFS was 10.9 months while patients received TLC as first line treatment showed longest median PFS of 20.7 months. Patients pretreated with trastuzumab showed a median PFS of 10.2 months. In patients who pretreated with trastuzumab, the continuation of trastuzumab on the basis of standard lapatinib plus capecitabine had a median PFS of 11.3 months. TL combined with capecitabine or vinorelbine showed no significant difference in median PFS, though TL combined with capecitabine had numerically prolongation (11.4 vs 8.5 months, p=0.231). Patients had brain metastasis (BM) also showed a median PFS (intracranial and extracranial lesions considered) of 10.6 months. Lines of systematic metastatic treatment was an independent predictive factor of PFS. The median OS was not reached. 277 patients were included in ORR analysis. ORR was 42.6%. Toxicities of triplet combinations were tolerable and the most common grade 3 and 4 adverse events were neutropenia (16.8%). Conclusions: TLC demonstrated promising effects and tolerable safety in HER2+MBC, even in patients with BM , providing a theoretical basis for clinical practice.